Regression mouse mammary tumour through complement-mediated inflammation of C5A/C5AR axis - Kamarudin, Nurul Hazwani (2015)
Complement component 5a (C5a) is a potent inflammatory chemoattractant that are triggered by the activation of the complement system. This complement might be a beneficial therapeutic target for the initiation of an effective anti-tumour response.The functional effect of C5a is exerted via its receptor, C5aR and this interaction of C5a/C5aR signaling is widely used in pharmaceutical studies. In the current study,C5aR was found to be expressed abundantly on the cell membrane of EMT6 cell line. C5a agonist, EP54 and antagonist, PMX205 were shown to be able to trigger the modulation of C5a by either promoting or inhibiting tumour development ofEMT6 murine mammary cancer cells through in vitro and in vivoexperiments. In the in vitro study, the cells treated with EP54haveasignificant reduction in cells proliferation with a low absorbance and percentage value in both Alamar Blue and MTT assay respectively as compared to PMX205 and chemotherapy drug, Tamoxifen which acts as a positive control. C5aR agonism and Tamoxifen treatments both contribute to the apoptotic activity as shown with the acridine orange (AO) and propidium iodide (PI) experiment. For the in vivo study, a group of female Balb/c mice injected with EMT6 cells line and treated daily with EP54 peptide showed a regression of tumour size after day 8 to day 14 post-treatment while for the group with PMX205 treatment showed an increased in tumour size. In order to analyze the role of C5a agonist and antagonist towards treated cultured cells and liver tissues, Enzyme Linked Immunosorbent Assay (ELISA) was conducted to quantify the levels of TNF-α, Caspase 3, C5a and Vascular Endothelial Growth Factor A (VEGF-α) signals following treatments. The data showed that EP54 significantly promoted high number and concentration of signaling proteins except VEGF-α, suggesting that the treatment diminishes tumour development and simultaneously generate activation of apoptotic activity. Both C5aR agonism and antagonism peptides might be suggested affecting several tissues in mice as treatments by both peptides have resulted in high concentration levels of the aspartate aminotransferase (AST), Urea, Creatinine and Creatine Kinase (CK) enzymes compared to the normal mice. In summary, C5a agonist,EP54 has a potential to minimized mammary tumour growth by activating the C5a/C5aR signaling and promotes apoptosis.